Self assessment of second level students' learning style - Jusoh, Zuraini; Roslan, Samsilah; Hassan, Roshafiza (Human Resources Management Academic Research Society (HRMARS), 2024)
Every student has a different learning style. To produce effective teaching and learning activities, teachers need to identify their students' learning styles. For that, this study was conducted to identify the learning style of second grade students in a classroom. A set of questionnaires modified from Chislett and Chapman (2005) was used to find out whether the studied students have a visual, auditory or kinesthetics learning style. A total of 32 students have been involved in this study consisting of various races. The selection of this group of students is made randomly, that is, the teacher is made sure to teach two second-level classes that are equivalent to their academic achievement. Using a simple random method, these two classes are determined to either represent the experimental group or the control group. Only the students of the experimental group underwent a learning style self-assessment test that will learn composing skills using different teaching modules. Once the student's learning style is identified, different teaching modules are created and used according to the student's learning style. However, for this paper, what will be discussed is the findings of the student self-assessment test which is the initial process of this quasi-experimental study. The results of the study show that more students studied have an auditory learning style, which is as many as 14 people. Meanwhile, the visual and kinesthetics learning styles were nine people each.